2002
DOI: 10.1556/select.3.2002.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Selection and Genetic Diversity in Humans

Abstract: Recent research into human origins has largely focused on deducing past events and processes from current patterns of genetic variation. Some human genes possess unexpectedly low diversity, seemingly resulting from events of the late Pleistocene. Such anomalies have previously been ascribed to population bottlenecks or selection on genes. For four species of matrilineal whale, evidence suggests that cultural evolution may have reduced the diversity of genes which have similar transmission characteristics to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The selection for increased LINE1 suppressors in the human lineage may be a consequence of a population bottleneck created by a combination of factors, such as pandemic pathogens or extreme climate change. A speculative hypothesis suggests that less (but not null) genomic variability in humans could have contributed to increased cultural evolution 79 .…”
Section: Box 1 | Evolutionary Impact Of Mobile Elementsmentioning
confidence: 99%
“…The selection for increased LINE1 suppressors in the human lineage may be a consequence of a population bottleneck created by a combination of factors, such as pandemic pathogens or extreme climate change. A speculative hypothesis suggests that less (but not null) genomic variability in humans could have contributed to increased cultural evolution 79 .…”
Section: Box 1 | Evolutionary Impact Of Mobile Elementsmentioning
confidence: 99%
“…However, this process is somewhat different from the culturally driven ecological speciation of killer whales, and the killer whale scenario is likely rare (20) and maybe unique. Cultural hitchhiking producing low genetic diversity may also be rare, because it requires quite stable groups of relatives with quite stable functionally important cultures producing consistent fitness differentials; cultural hitchhiking works much more efficiently if the cultural groups are sympatric (26,57).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, models have shown that the remarkably low levels of human genetic diversity could result from culturally mediated population structure (25) or from selectively important cultures being transmitted in parallel with neutral genes (26). However, there is no strong empirical evidence for either of these processes.…”
mentioning
confidence: 99%
“…Whitehead and colleagues (31) have shown that cultural hitchhiking suppresses genetic diversity in structured populations when genes and cultural traits are transmitted symmetrically, gene flow is low, intergroup cultural transmission is rare, and cultural evolution is rapid. However, their model of Late Pleistocene humans assumes that cultural traits-not genesdirectly and substantially affect reproductive fitness, such that ''culturally advanced'' groups outcompete others.…”
Section: Discussionmentioning
confidence: 99%